The Dress Code for Muslim Women: A Linguistic Analysis of the Qurānic Verses and the Prophetic Traditions - Musharraf, Muhammad Nabeel; Dars, Basheer Ahmed; Arshad Munir (Journal of Islamic and Religious Studies, 2018)
It is not uncommon to find cases of Muslim women being harassed or bullied in many of the Muslim-minority countries because of their dress. These Islamophobic attacks, unfortunately, are not merely conducted by radicalised individuals; but the subjugation of the rights of Muslim women also comes from institutional bodies and governments. Secular nations, such as France, Germany, Italy, Belgium, Netherlands, Bulgaria, Switzerland, USA, UK, Canada, China, and Russia have either imposed restrictions on Muslim women regarding their dress code. They see veil as a non-acceptance of progressive or cumulative values which is unsurprisingly not welcomed by the Muslim community. In such environment, it is inevitable for the Muslims to understand what the Qur’ān and Sunnah really say about the dress code for Muslim women in order to explain what their religion really requires from them and to communicate it appropriately to the government officials, journalists, politicians, and other relevant stakeholders. It is also essential from the perspective of segregating cultural aspects from the religious aspects. Many of the commonly used words for the dressing of Muslim women are more rooted in culture than the religion. It is accordingly vital to understand what the Qur’ān and Sunnah really command about the women dressing and how it has been interpreted in various Islamic societies and cultures. This paper accordingly presents an analysis of all the relevant Qur’ānic verses and the prophetic traditions (from the 6 most renowned books of ahadith). The linguistic analysis employed in this paper results in the identification of items of dress that were worn by Muslim women to safeguard their modesty during the times of Prophet Muhammad (ﷺ). The same principles are relevant for today’s age and time and the Muslims can use those guidelines to delineate cultural practices from the religious injunctions.